Students Self Efficacy: Do Perceived Information Technology Competencies Andwork Readiness Matter? - Dr. Sukirno; Aisyah, Prof.Mimin Nur; Syaban, Prof. Ponty; Novitasari, Prof Budi Tiara; Shaikh, Dr. Mohsin (The journal of contemporary issues in business and government, 2021)
Management education is currently facing new challenges that arise as a result of globalization, technological developments and weak ethics. This study aims to map the information technological competency and work readiness of accounting students and their influence on student self-efficacy in the digital era. This research used a quantitative approach. The respondents of this research were 106 students of the Accounting Study Program at Faculty of Economics Yogyakarta State. Data was collected using a semi open ended questionnaire which was circulated to students online. The data obtained were analyzed using qualitative descriptive analysis techniques through stages of reduction, presentation, and drawing conclusions. Path analysis is also used to analyze the direct and indirect effect of accounting students’ information technological competency variables on work readiness and self-efficacy. Based on the data analysis, it was concluded that the highest Work Readiness was owned by students at the age of 20 years. There were no significant differences between the Information technological competency, Work Readiness, and self-efficacy levels. Based on the path analysis test, it is concluded that there is a direct effect of Information technological competency on Self Efficacy (-0.021), however, the effect on self-efficacy is not mediated by Work Readiness.